2023
DOI: 10.3389/frph.2023.1130849
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and small extracellular vesicle mediated-intracellular communication in the peritoneal microenvironment: Impact on endometriosis development

Abstract: Endometriosis is an inflammatory disease that is defined as the growth of endometrium-like tissue outside the uterus, commonly on the lining of the pelvic cavity, visceral organs and in the ovaries. It affects around 190 million women of reproductive age worldwide and is associated with chronic pelvic pain and infertility, which greatly impairs health-related life quality. The symptoms of the disease are variable, this combined with a lack of diagnostic biomarkers and necessity of surgical visualisation to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 104 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…EMs is known to be an inflammatory disease. Studies have found that the presence of a large number of macrophages in the peritoneal fluid of patients with EMs can release more pro-inflammatory cytokines such as IL and TNF-α to participate in the intercellular communication modification, promote fibroblast mitosis, adhesion and maintain the adhesion of ectopic endometrial tissue ( 2 , 34 ). In the present study, the serum levels of TNF-α and IL-1β were upregulated in the model group.…”
Section: Discussionmentioning
confidence: 99%
“…EMs is known to be an inflammatory disease. Studies have found that the presence of a large number of macrophages in the peritoneal fluid of patients with EMs can release more pro-inflammatory cytokines such as IL and TNF-α to participate in the intercellular communication modification, promote fibroblast mitosis, adhesion and maintain the adhesion of ectopic endometrial tissue ( 2 , 34 ). In the present study, the serum levels of TNF-α and IL-1β were upregulated in the model group.…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis mainly targets the pelvic organs and peritoneum, with common sites being the ovaries, ligaments, and fallopian tubes for intra-peritoneal locations, and areas like the cervical portio and abdominal scars for extraperitoneal locations. It infrequently affects extra abdominal organs such as the lungs and urinary system [3] .…”
Section: Endometriosismentioning
confidence: 99%